Exploring the structure, regulation, and function of the surface tethered Pseudomonas aeruginosa virulence factor, AaaA, and its role in maintaining chronic wound infections - Laxton, Claire. S. (2023)
Pseudomonas aeruginosa is a leading cause of bacterial wound infections and is associated with disproportionately high mortality in burn patients, and morbidity in immunosuppressed and diabetic people, due to its ability to establish chronic wound infections. In this study, an in vitro synthetic wound model was used to examine the role of arginine-specific aminopeptidase of P. aeruginosa A (AaaA), a highly conserved, surface-tethered autotransporter which is known to be important for virulence during murine chronic wound infections. AaaA has potential as an antimicrobial drug or vaccine target due to its accessibility and immunogenicity, yet its mechanism of action is unclear. It is known that AaaA cleaves N-terminal arginine from peptides, which serve as a nutrient source in the oxygen and nutrient-limited environments of chronic wounds. Additionally, arginine can act as a signalling molecule in biofilm regulation, and it not yet clear what role AaaA may play in this regard. This study aimed firstly, to elucidate the structure and conservation of AaaA using both bioinformatic tools and by purifying AaaA for crystallography, and secondly to probe the gene expression and function of AaaA in a synthetic chronic wound (SCW) model. In this study, AaaA was found to be highly conserved, with zero missense mutations in its active site residues in over 3000 P. aeruginosa genomes. A few, likely non-deleterious amino acid substitutions were identified to be common in almost all genomes except for PAO1, highlighting the deviation of this lab strain from other P. aeruginosa isolates. Some progress was made towards purifying a truncated version of AaaA, which did not contain the membrane-localising β-barrel, with some evidence that it exists as both a monomer and an SDS-resistant dimer, though further verification is needed. Using transcriptional reporters and enzymatic AaaA activity assays, this study showed that AaaA is preferentially upregulated in the SCW, compared to in planktonic culture. AaaA was also shown to confer a modest but significant survival advantage in the SCW, as seen previously in vivo. This highlights the usefulness of this more disease-relevant model in studying important virulence factors which have marginal phenotypes in planktonic conditions. Analysis using RT-qPCR showed that rpoS, but not arginine metabolism genes, was upregulated ~3-fold in an aaaA mutant, suggesting that loss of aaaA leads to an increased starvation response. Transcriptomics by RNA-Seq identified further quorum-sensing and RpoS-repressed genes involved in phenazine and alkyl-quinolone production, as well as possible chronic-infection-specific virulence factors, which were downregulated in the aaaA mutant, possibly as a result of increased RpoS expression. This is the first time a link between AaaA and RpoS has been demonstrated, both of which have likely distinct roles in nutrient foraging, potentially on either axis of acute or chronic infection phenotypes. Further study, particularly using proteomics, is required to better understand this relationship and how it relates to the growth differences seen in the aaaA mutant in the SCW. Using a colorimetric quantification assay, no difference in extracellular arginine between wild-type and aaaA mutant-infected SCWs was detected. However, arginine levels in uninfected SCWs were ~3-fold higher, suggesting that arginine is being utilised in the SCW. A higher resolution approach, such mass spectrometry is required to detect differences related to AaaA. Finally, the Spytag-Spycatcher tagging system was used to localise AaaA in P. aeruginosa at the single cell level, with the potential that this technology could be used to localise AaaA in a multi-species biofilm in the future. In summary, this study has created a number of tools for studying AaaA in chronic wound infections, including validating the use of the SCW. It has also uncovered new links between AaaA, RpoS and quorum sensing, to create an updated model of AaaA regulation in a chronic wound environment.